Galileo Engineer - Valleriani, Matteo. author. (orcid)0000-0002-0406-7777 Link aut Link
XXII, 320 p.
Keywords: This work systematically investigates and reconstructs the practical knowledge Galileo shared during his lifetime. Galileo shared many aspects of practical knowledge.These included the methods and experience of foremen and engineers active within various frameworks. Galileo did not always react to such scientific impulses in the same way. On the one hand, he not only shared practical knowledge, but also acted as an engineer, especially within the framework of the art of war at the end of the sixteenth century, and more so during the time he spent in Padua. On the other hand, his scientific achievements were largely based on and influenced by aspects of practical knowledge coming from particular disciplines and activities, without him ever becoming an expert in these disciplines. Two case studies, the first concerned with Galileo's theory of the strength of materials and the second with his achievement of an atomistic heat doctrine, enable a focus onthe early modern model of generation of new scientific knowledge based on the conflicting interaction between aspects of practical knowledge and Aristotelian theoretical assumptions.